Biomechanical Simulation Analysis and Experimental Study of Puncture Force in Arteriovenous Fistula for Hemodialysis - Song Liu; Yaqin Wang; Yi Wang; Jun Su; Bingrong Liu; Ling Peng (Journal of Applied Science and Engineering, 2026)
Objective: To investigate the common complications of arteriovenous fistula (AVF) puncture during hemodialysis, to deeply study the mechanical mechanism of the puncture process, and to provide a theoretical basis for optimizing puncture techniques and designing new puncture devices. Methods: The puncture process was divided into five stages, and the force conditions of each stage were analyzed. Mechanical models of puncture resistance, friction, and cutting force were established. Finite element simulation was used to simulate the stress distribution under different puncture conditions. An AVF puncture experimental platform was built to collect mechanical data under different puncture parameters, and the simulation results were verified. Results: The simulation and experimental results showed that the smaller the diameter of the puncture needle, the smaller the puncture force. Within the puncture angle range of 15-30°, the puncture force increased with the increase of the angle, reaching a peak at 30°. The puncture speed had little effect on the puncture force within the range of 1-5 mm/s. In clinical practice, for patients with thinner vascular walls, a puncture needle with a diameter of less than 1 mm should be selected, and a puncture angle of 25-30° should be used. Conclusion: This study reveals the mechanical characteristics of the AVF puncture process and provides theoretical guidance for optimizing puncture techniques and reducing the risk of complications. The research results can provide key parameters for the development of hemodialysis AVF puncture robots.